Peculiarities of britlle and ductile materials destruction and deformation during the explosion of industrial shaped charges - Voitenko, Yu.; Kravets, V.; Shukurov, A.; Drachuk, O. (Розробка родовищ, 2017)
Purpose. To study the laws of deformation and destruction of brittle and ductile rocks and concretes under explosion of industrial shaped charges. Findings. The work describes the experimental data on the destruction of barriers made of concrete, granite, steel ST 3, AMC-n alloy, and zinc by the explosions of shaped charges of serial production with porous liners. Calculation formulas for estimating the radius of a destruction zone of geomaterials and rocks in case of a semi-infinite barrier are suggested. The calculation method is based on the estimation of energy impact on the rock by jet penetration velocity into the barrier. Jet velocities are determined experimentally and by engineering methods. The reasons for deviations in the hole shape and deflection of the destruction zone from the symmetry axis were determined. Мета. Дослідження закономірностей деформування й руйнування крихких і пластичних гірських порід та бетонів при вибуху промислових кумулятивних зарядів. Результати. В роботі описані експериментальні дані про деформацію та руйнування перешкод з бетону, граніту, пінобетону, сталі Ст 3, сплаву АМЦ-н і цинку вибухами кумулятивних зарядів серійного виробництва з пористим облицюванням. Запропоновано розрахункові формули для оцінки радіусу зони руйнування геоматеріалів і гірських порід у разі напівнескінченної перешкоди. Визначено причини відхилень форми отвору і зони руйнування від осі симетрії. Цель. Исследование закономерностей деформирования и разрушения хрупких и пластичных горных пород и бетонов при взрыве промышленных кумулятивных зарядов. Результаты. В работе описаны экспериментальные данные о деформировании и разрушении преград из бетона, гранита, пенобетона, стали Ст 3, сплава АМЦ-н и цинка взрывами кумулятивных зарядов серийного производства с пористыми облицовками. Предложены расчетные формулы для оценки радиуса зоны разрушения геоматериалов и горных пород в случае полубесконечной преграды. Определены причины отклонений формы отверстия и зоны разрушения от оси симметрии.